2012
DOI: 10.1071/wr12114
|View full text |Cite
|
Sign up to set email alerts
|

An eDNA approach to detect eastern hellbenders (Cryptobranchus a. alleganiensis) using samples of water

Abstract: Context Environmental DNA, or eDNA, methods are a novel application of non-invasive genetic sampling in which DNA from organisms is detected via sampling of water or soil, typically for the purposes of determining the presence or absence of an organism. eDNA methods have the potential to revolutionise the study of rare or endangered taxa. Aims We evaluated the efficacy of eDNA sampling to detect populations of an amphibian of conservation concern, the eastern hellbender (Cryptobranchus a. alleganiensis), indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
122
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 42 publications
4
122
2
1
Order By: Relevance
“…Comparisons of conventional and eDNA surveillance methods already have been made (e.g., Goldberg et al 2011, Jerde et al 2011, Thomsen et al 2011, Olson et al 2012, but methods were rarely applied simultaneously or were focused on 1 species only , Pilliod et al 2013. We found that the taxon-specific match of the 2 methods was moderate to high (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Comparisons of conventional and eDNA surveillance methods already have been made (e.g., Goldberg et al 2011, Jerde et al 2011, Thomsen et al 2011, Olson et al 2012, but methods were rarely applied simultaneously or were focused on 1 species only , Pilliod et al 2013. We found that the taxon-specific match of the 2 methods was moderate to high (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…We found iDNA sequences from multiple copepods sampled from the same whale shark host to be identical, suggesting copepods have a persistent, long-term association with their host shark, which contrasts with the more generalist and mobile host associations of other invertebrate ectoparasites in terrestrial and aquatic ecosystems, such as leeches, blow flies, and mosquitoes (Calvignac-Spencer et al, 2013). However, these findings should be treated with some degree of caution and a multi-locus approach using microsatellite Frontiers in Marine Science | www.frontiersin.org markers (Olson et al, 2012) might offer a more powerful means to validate these findings. As reported by Vignaud et al (2014), our estimates of genetic structure across the Indian, Pacific, and Atlantic oceans indicated the presence of two distinct populations, one in the Indo-Pacific and the other in the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…While recent studies have demonstrated that eDNA is a powerful tool for detecting target species in aquatic ecosystems [11], the majority of studies to date focus on detection from water in mesocosms [2,[12][13][14][15][16] or experimental/ natural ponds [1,[7][8][9]11,12,16]. A few studies have used eDNA survey methods in stream or river water samples for detection of amphibians [9,15,17], molluscs [18], fish [6,9,13,19] and invertebrates [20].…”
Section: Introductionmentioning
confidence: 99%